UPAYA GO-JEK DALAM MENINGKATKAN EKSPANSI BISNIS INTERNASIONAL DI VIETNAM TAHUN 2018-2022 - Utari, Febrianti; Pakpahan, Saiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Go-Jek is an Indonesian-born start-up company that has expanded to several countries in Southeast Asia. Go-Jek entered Vietnam by investing in go-viet, expanding with the local brand